Effect of dietary iron supplementation on the equine fecal microbiome - Arantes, Julia Assis; Borges, Alexandre Secorun [UNESP]; Zakia, Luiza Stachewski; Surette, Michael Gordon; Weese, Jeffrey Scott; Costa, Marcio Carvalho; Arroyo, Luis Guillermo (My University, 2023)
Iron is an essential element for all living organisms, including bacteria, as several virulence factors and replication components are influenced by iron concentration. The objective of this study was to determine whether the composition and diversity of the fecal microbiota of adult horses are affected by supplemental dietary iron. Ten clinically healthy horses were randomly divided into a control and an iron-supplemented group (n = 5). The treated group was supplemented with oral ferrous sulphate monohydrate (720 ppm of iron), whereas the control group received 320 ppm of iron daily for 15 d. Fecal samples were collected before and 5, 10, 15, and 30 d after supplementation and frozen at-80°C. DNA was sequenced using an Illumina MiSeq platform and data were analyzed using the software Mothur and linear discriminant analysis (LDA) effect size (LEfSe). Iron supplementation caused no change in the overall composition of the fecal microbiota, but some minor changes were observed in the low-abundant bacteria, as well as an increased alpha diversity after 15 d of supplementation. Significant differences in community composition of the fecal microbiota over time were observed in both groups, highlighting the importance of a control group, as there are variables that cannot be controlled in microbiome studies.